1979
DOI: 10.1002/cpt1979261122
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and excretion of tolmetin in arthritic patients

Abstract: The absorption, kinetics, biotransformation, and excretion of tolmetin and its metabolites were studied in patients with rheumatoid arthritis (RA) to evaluate the effects of the disease on tolmetin disposition. Five RA patients were stabilized on tolmetin sodium (300 mg, 4 times daily for 14 days) before receiving a single oral solution dose of tolmetin-14C sodium (300 mg as the acid) on day 15. Tolmetin was rapidly and completely absorbed (peak time, 20 to 60 min) and eliminated rapidly from plasma with a bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1982
1982
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…In unpublished work with individuals on long term tolmetin therapy suffering from rheumatoid synovitis of the knee, Desiraju et al (1982) found a tolmetin half-life of 6 hours in serum and 7.2 hours in synovial fluid. The observed serum half-life from these studies is substantially greater than that obtained in other reports of tolmetin pharmacokinetics (Cressman et al, 1976;Grindel et al, 1979).…”
Section: Tolmetincontrasting
confidence: 66%
“…In unpublished work with individuals on long term tolmetin therapy suffering from rheumatoid synovitis of the knee, Desiraju et al (1982) found a tolmetin half-life of 6 hours in serum and 7.2 hours in synovial fluid. The observed serum half-life from these studies is substantially greater than that obtained in other reports of tolmetin pharmacokinetics (Cressman et al, 1976;Grindel et al, 1979).…”
Section: Tolmetincontrasting
confidence: 66%
“…On day 8, after a single 400-mg dose of tolmetin, blood and synovial fluid samples were obtained repeatedly for 24 hr. Blood (10 ml) were taken just prior to receiving the medication and then at 5, 15, 30, and 45 min and 1, 1.5, 2, 4, 6, 8,12,16,20, and 24 hr after the dose. The synovial fluid (2 ml) was sampled just prior to and 2, 8, 12, and 24 hr after the drug dose.…”
Section: Methodsmentioning
confidence: 99%
“…However, with only five data points, it is impossible to specifically model the synovial fluid kinetics of tolmetin. The average terminal synovial fluid t% of 6.9 + 2.3 hr was derived from only three points (8,12, 24 hr after the last dose). There were no significant differences between the terminal t %~ in plasma and synovial fluid (Student's paired t test).…”
Section: Patientmentioning
confidence: 99%
“…Grindel et al (1979) found a significant increase in the renal clearance of tolmetin in arthritic patients. They concluded that a concomitant increase in Vd secondary to reported decreases in the plasma protein binding of tolmetin is the most likely explanation for the increased renal clearance of the drug.…”
Section: Tolmetinmentioning
confidence: 95%